Is benchmarking appropriate for the management of elite sport systems? - Böhlke, N.; Robinson, L. (2009)
In recent times the concept of benchmarking has been advocated as a tool for improving management within the sport industry. For example, it is an underpinning principle of the UK Labour government`s drive for efficiency and effectiveness (Audit Commission, 2000), leading to the emergence of the National Benchmarking Service promoted by Sport England, the lead body for sport in England. However, the sector of sport management in which benchmarking has been most utilized is that of the management of elite sport systems where benchmarking has been considered as a good method of identifying the factors that lead to international sporting success. `Elite sport system` is the term used to describe the infrastructure and processes used by a sport to identify, develop and prepare athletes for international sporting success. This approach to sport is conceived as a system as it begins with the identification of raw talent that is transformed by a number of factors into athletes which can achieve success on the elite sport stage. In the past decade these sport systems have become the focus of much benchmarking investigation (de Bosscher, de Knop, van Bottenburg, and Shibli, 2006, 2008; Green, 2007a; Green and Oakley 2001) primarily as a consequence of two major events. The first was the sporting success achieved by the former German Democratic Republic (GDR) during the 1970s and 1980s, which showed that an organised approach towards the support of high performance sport could result in the systematic production of successful international athletes. The second, and perhaps more important event, was the success the Australian Institute of Sport (AIS) enjoyed in the build up to the 2000 Olympic Games. As the main elements of the AIS were based on the GDR system, this suggested that it was possible to achieve success by benchmarking elite sport systems against the infrastructure and processes to be found in other successful sporting nations. Benchmarking has been successfully used in many conventional management contexts to improve performance by investigating the practices of superiorly performing organisations (Brownlie, 1999; Camp 1989, 1995, 1998; Carpinetti and de Melo, 2002; Cuadrado, Frasquet and Cervera, 2004). Underpinning the benchmarking approach is the concept of learning from best practice and this approach seeks to improve practice as a consequence of a detailed analysis of the practices used in successful organisations which are then introduced into an organisation wishing to improve success. Therefore benchmarking can be advocated as a means of allowing managers to improve management of their elite sport systems by understanding how other successful systems operate. Benchmarking has a number of forms. In their review of benchmarking in the UK, Hinton, Francis and Holloway (2000, p. 53) set out the following typology developed by Camp (1995) as a means of classifying benchmarking activities: · Internal. A comparison among similar operations within one`s own organisation. · Competitive. A comparison with the best of the direct competitors. · Functional. A comparison of methods with those of companies with similar processes n the same function outside one`s industry. · Generic process. A comparison of work processes with others who have innovative, exemplar work processes. This is the form of benchmarking that was chosen for the research presented here. It is apparent from research in this field (de Bosscher et al., 2006; 2008; Houlihan and Green, 2008; Oakley and Green, 2001) that benchmarking has promoted a convergence of elite sport systems as many nations have sought to copy what has been perceived to contribute to the success of the GDR and AIS systems. Indeed it is possible to observe a "trend towards a homogenous model of elite sport systems" (Oakley and Green, 2001, p. 91) across different sports and different nations. However, despite this convergence, it is clear there are countries that perform consistently better in some sports than other countries do, such as Australian cricket and British cycling. Thus, as most contemporary elite sport systems are made up of similar infrastructure and practices, it appears that the actual design of these systems can no longer explain differences in success. Therefore it is possible to argue that the management and delivery of an elite sport system is now a more important factor for success than the mere existence of such a system. Thus, if sports wish to improve success, managers of elite sport systems should focus on improving the way the system is delivered - the processes followed - in order to enhance the output of successful athletes. Knowledge of how to do this is limited and therefore the research set out in this paper aimed to evaluate the applicability of the concept of process benchmarking as a tool for improving the management of elite sport systems. Process benchmarking requires a consideration of exemplar work processes and consequently, a number of the processes of the successful elite systems of the Swedish Athletics Association and the Norwegian Skiing Federation went through a benchmarking process. This paper sets out the findings of this research and begins by presenting an overview of elite sport systems. It then moves on to discuss the concept of benchmarking, followed by an outline of the method used in the study. The results of the research are presented and the paper ends with a discussion of the usefulness of process benchmarking for the management of elite sport systems.